Effect of preparation conditions on the properties of ZIF-8@ZnO PEO coating - Valeryia Kasneryk; Hauke Rohr; Qianqian Chen; D.C.Florian Wieland; Anton Davydok; Eugen Gazenbiller; Maria Serdechnova; Carsten Blawert; Norbert Stock; Mikhail L. Zheludkevich (Journal of Materials Research and Technology)
Recently, metal organic frameworks (MOFs), crystalline porous materials, demonstrated their effectiveness for the post-modification of coatings obtained by plasma electrolytic oxidation (PEO) treatment. The post-modification leads to the sealing of PEO porosity as well as endowing the coating with active corrosion protection ability. In the current work, ZnO-based PEO coatings on the surface of Z1 Zn alloy was partially converted into ZIF-8 by treatment with vapours of 2-methylimidazole (2-HmIm). It was found that the degree of PEO-to-ZIF-8 conversion and the size of the ZIF-8 particles increased with an increase in temperature from 120 to 150 °C, and with an extension of the treatment with 2-HmIm from 5 h to 60 h. Furthermore, the sealing of the PEO pores can be controlled by applying different treatment conditions. It was also found that such treatments resulted in the enhancement of the corrosion resistance of the materials. However, the key factor determining the performance of the final ZIF-8@PEO hybrid coatings was a balance between the level of ZnO-based PEO dissolution and crystallisation of ZIF-8 phase.